220 Electrocardiographic findings and mortality in COVID-19 patients hospitalized in different clinical settings. (8th December 2021) - Mele, Marco; Tricarico, Lucia; Vitale, Enrica; Favia, Andrea; Croella, Francesca; Alfieri, Simona; Corbo, Maria Delia; Mango, Federica; Casavecchia, Grazia; Brunetti, Natale Daniele
Abstract: Aims: 12-lead electrocardiogram (ECG) still represents the first line approach for cardiovascular assessment even in patients with COVID-19. We therefore sought to describe and compare ECG findings in three different hospital settings: intensive care unit (ICU) (invasive ventilatory support), respiratory care unit (RCU) (non-invasive ventilatory support) and Covid-19 dedicated internal medicine unit (IMU) (oxygen supplement with or without high flow). Methods and results: We retrospectively analysed the 12-lead ECGs of 1124 consecutive patients hospitalized for respiratory distress and COVID-19 in a single III level hospital. Age, gender, main clinical data and in-hospital survival were recorded. 548 patients were hospitalized in IMU, 361 in RCU, 215 in ICU. Arrhythmias in general were less frequently found in RCU (16% vs. 26%, P < 0.001). Deaths occurred more frequently in ICU patients (43% vs. 20–21%, P < 0.001). After pooling predictors of mortality (age, intensity of care setting, heart rate, ST-elevation, QTc prolongation, Q-waves, right bundle branch block, and atrial fibrillation), the risk of in-hospital death can be estimated by using a derived score. Three zones of mortality risk can be thus identified: <5%, score <5 points; 5–50% score 5–10, and >50%, score >10 points. The accuracy of the score assessed at ROC curve analysis was 0.791. Conclusions: ECG differences at admission con be found in COVID-19 patients according to different clinical settings and intensity of care. A simplified score derived from few clinical and ECG variables may predict in-hospital mortality with a good accuracy.